Reversible Environmental Catastrophes with Disconnected Generations - Ben J. Heijdra; Pim Heijnen (Center for Economic Studies and ifo Institute (CESifo), 2018)
We study environmental policy in an economy-ecology model featuring multiple deterministic stable steady-state ecological equilibria. The economy-ecology does not settle in either of the deterministic steady states as the environmental system is hit by random shocks. Individual live for two periods and derive utility from the (stochastic) quality of the environment. They feature warm-glow preferences and therefore will engage in private abatement in order to slightly influence the stochastic process governing environmental quality. The government may also conduct abatement activities or introduce environmental taxes. We solve for the market equilibrium abstracting from public abatement and taxes and show that the ecological process may get stuck for extended periods of time fluctuating around the heavily polluted (low quality) deterministic steady state. These events are called environmental catastrophes. They are not irreversible, however, as the system typically switches back to the basin of attraction associated with the good (high quality) deterministic steady state. The paper also compares the stationary distributions for environmental quality and individuals' welfare arising under the unmanaged economy and in the first-best social optimum.
Keywords: D60; E62; H23; H63; Q20; Q28; Q50; 330; ecological thresholds; nonlinear dynamics; environmental policy; abatement; capital taxes